Effect of vitamin C and lipoic acid on streptozotocin-induced diabetes gene expression - Sadi, Goekhan; Yilmaz, Oekkes; Guray, Tuelin (Springer, 2008)
The involvement of oxidative stress in the pathogenesis of diabetes mellitus has been confirmed by numerous studies. In this study, the expression of two antioxidant enzymes, superoxide dismutase (SOD), and catalase which are involved in the detoxification of reactive oxygen species was studied in the streptozotocin-induced diabetic rat liver tissues. The enzyme assays showed a significant decrease in both enzymes activities compared to control animals. The RT-PCR and Western-blot analysis results demonstrated that this decrease in activity is regulated at the level of gene expression, as both catalase and Cu-Zn SOD mRNA and protein expressions were also suppressed. Supplementing the animals with vitamin C, a powerful antioxidant increased both SOD and catalase activities with no change in both mRNA and protein expressions suggesting a role of post-translational modification. However, even though mRNA expressions of both catalase and Cu-Zn SOD were not changed, the protein levels increased in parallel to activities in the case of another antioxidant, alpha-lipoic acid. An increase in the rate of translation, without changing the rate of transcription indicates a translational effect of lipoic acid in changing the activities of antioxidant enzymes to prevent the oxidative damage in diabetes.
Keywords: diabetes; antioxidants; gene expression; lipoic acid; vitamin C